The Impact of the Consistency of Child Witness and Peer Reports on Credibility - Dykstra, Victoria W. (Journal of interpersonal violence, 2023)
Adults’ perceptions of children’s disclosures have important implications for the response to that disclosure. Children who experience adult transgressions, such as maltreatment, often choose to disclose this experience to a peer. Thus, peer disclosure recipients may transmit this disclosure to an adult or provide support for the child’s own disclosure. Despite this, the influence of peer disclosure on a child witness’s credibility, as well as on the perceptions of peer disclosure recipients, is unknown. The present study examined how child witnesses’ and peer disclosure recipients’ credibility is impacted when the peer either confirms or contradicts the witness’s disclosure (or concealment) of an adult transgression. Participants listened to a child witness and peer being interviewed by an adult in one of four disclosure patterns (consistent disclose, consistent conceal, witness disclose/peer conceal, or witness conceal/peer disclose). Participants rated both the witness and the peer on dimensions of credibility (honesty and cognitive competence). Results revealed that both the witness and peer were more credible when their reports were consistent with one another. When inconsistent, the witness/peer who disclosed was considered more credible than the one who concealed. The findings indicate the potential importance of peers in the disclosure process as they may support the witness’s report and even be a credible discloser when the witness is reluctant to disclose.